2011
DOI: 10.1103/physrevb.83.104508
|View full text |Cite
|
Sign up to set email alerts
|

Se77NMR investigation of theKxFeet al.

Abstract: We report comprehensive 77 Se NMR measurements on a single crystalline sample of the newly discovered FeSe-based high temperature superconductor KxFe2−ySe2 (Tc = 33 K) in a broad temperature range up to 290 K. Despite deviations from the stoichiometric KFe2Se2 composition, we observed 77 Se NMR lineshapes as narrow as 4.5 kHz under a magnetic field applied along the crystal c-axis, and found no evidence for co-existence of magnetic order with superconductivity. On the other hand, the 77 Se NMR lineshape splits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
85
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 37 publications
15
85
0
Order By: Relevance
“…2(a) which were already observed in previous reports [12,14,15]. As 87 Rb is a spin 3/2 nucleus, the spectrum consists of a central line (nuclear transition 1/2↔-1/2) and two quadrupolar satellites (nuclear transitions ±3/2↔±1/2) due to the local electric field gradient (EFG).…”
supporting
confidence: 62%
See 2 more Smart Citations
“…2(a) which were already observed in previous reports [12,14,15]. As 87 Rb is a spin 3/2 nucleus, the spectrum consists of a central line (nuclear transition 1/2↔-1/2) and two quadrupolar satellites (nuclear transitions ±3/2↔±1/2) due to the local electric field gradient (EFG).…”
supporting
confidence: 62%
“…However, the 77 Se hyperfine coupling to Fe spins is twice as large as that of 87 Rb, which implies that this AF Se signal would be 2 times broader and with a transverse relaxation T 2 which is 4 times shorter. Such a short T 2 of only a few s makes the signal impossible to detect in standard NMR pulse experiments, which explains why it has not been observed, neither by us nor by other groups [12,14,15].…”
Section: Scmentioning
confidence: 89%
See 1 more Smart Citation
“…The singlet, [91] nodeless, and isotropic nature of the pairing has been observed by numerous experiments. [64][65][66] Again, based on the sign-reversal properties of this d-wave gap, random-phase approximation (RPA)-based susceptibility calculation has predicted the presence of a spin-resonance mode, [22] which is observed later by inelastic neutron scattering measurement. [67] The unitary transformation of the FS and the pairing symmetry to the 2FUC is more interesting.…”
Section: Similarity Between Kfe 2 As 2 and Cecoin 5 Superconductorsmentioning
confidence: 99%
“…[4][5][6] In this case, the electron-pocket at M point is eliminated by increasing number of iron-vacancies in the non-stoichiometric K y Fe 2-x Se 2 crystal. [61][62][63] Both theories [22,50,52] and experiments [64][65][66] have demonstrated that isotropic and nodeless d-wave pairing is energetically favourable in this case, originating from intra-electron-pockets nesting. Our theoretical prediction of the spin-resonance [22] as a result of such nesting, has been observed recently by inelastic neutron scattering measurement.…”
Section: Introductionmentioning
confidence: 99%